Composite electrode and preparation method thereof

The surface of high-nickel positive electrode material is pre-covered through the carbon-assisted dry mechanical fusion process and combined with lithiated perfluorosulfonic acid polymer material to form a composite positive electrode sheet, which solves the reduction in cycle life of high-nickel positive electrode material and adhesive agent The selection problem has achieved high-speed capacity maintenance and charging and discharging performance improvement.

CN119181767APending Publication Date: 2024-12-24ADVANCED LITHIUM ELECTROCHEMISTRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310744946.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The high nickel content in the positive electrode materials of the existing lithium-ion secondary battery leads to a decrease in cycle life, and traditional surface modification methods are difficult to obtain a uniform coating and increase production costs. Improper selection of adhesives affects performance.

Method used

The surface of high-nickel positive electrode material is pre-covered by the carbon-assisted dry mechanical fusion process, combined with lithiated perfluorosulfonic acid polymer material, to form a composite positive electrode sheet, replace traditional adhesives, improve hydrophobicity and coating properties, and improve Charging and discharge performance.

Benefits of technology

The capacity maintenance rate is optimized at high magnification, which improves cycle life and charge and discharge performance, and provides a fast, effective adhesive and uniformly coated functional coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181767A_ABST
    Figure CN119181767A_ABST
Patent Text Reader

Abstract

The invention discloses a composite electrode and a preparation method thereof. The composite electrode is coated on a bearing surface of an electrode plate by a composite positive electrode material layer. The composite positive electrode material layer comprises a plurality of positive electrode material particles, first conductive carbon and a Li-Nafion material. The plurality of positive electrode material particles are made of a ternary material, the composition of the ternary material is Li [NixCoyMnz] O2, and x + y + z = 1, 0.8 lt; xlt; 1, 0lt; yt; Yt; 0, 0, 0, 0; zlt, zlt; and 0.2 part. The surfaces of the plurality of positive electrode material particles are coated with the first conductive carbon in advance through a dry mechanical mixing method. The weight percentage of the first conductive carbon relative to the plurality of positive electrode material particles ranges from 1 wt.% to 5.5 wt.%. The Li-Nafion material coats the surfaces of the plurality of positive electrode material particles and is bonded among the surfaces of the plurality of positive electrode material particles. The weight percentage of the Li-Nafion material relative to the plurality of positive electrode material particles ranges from 10 wt.% to 20 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode for a secondary battery, and more particularly to a composite electrode suitable for a secondary battery and a preparation method thereof. A composite positive electrode sheet is prepared by surface pretreatment of a carbon-assisted dry process and then combined with a lithiated perfluorosulfonic acid polymer material to enhance high-rate charging and discharging performance and optimize capacity retention rate. Background Art

[0002] In recent years, people's performance requirements for electric vehicles and energy storage devices have gradually increased, and the secondary batteries used in them are also required to have good performance. Among the many types of batteries, lithium-ion batteries using ternary positive electrode materials such as nickel-cobalt-manganese (NCM) have the characteristics of high capacitance and have become the current mainstream choice.

[0003] Since the nickel content in the above positive electrode materials is proportional to their energy density, and the price of cobalt metal fluctuates violently, the current mainstream development trend is to increase the nickel content in the positive electrode materials to increase energy density and reduce manufacturing costs. However, high-nickel positive electrode materials themselves are prone to negative reactions with electrolytes due to their high nickel content, resulting in a decrease in cycle life.

[0004] Traditional high-nickel materials are mostly modified by surface modification with inorganic metal oxides. However, it is difficult to obtain a uniform and complete coating through normal engineering means. And if the liquid phase metal oxide coating process is used, the selection and recovery of the solvent must be evaluated. Even a second heat treatment process is required. This greatly increases the process and cost of material production.

[0005] On the other hand, in the process of making positive electrode materials of lithium-ion secondary batteries into electrodes, binders are also indispensable key components. Improper selection of binders may affect the performance of positive electrode materials in electrodes after surface modification.

[0006] In view of this, it is necessary to provide a composite electrode suitable for secondary batteries and a preparation method thereof. By preparing a composite positive electrode sheet through surface pretreatment of a carbon-assisted dry process and then using a lithiated perfluorosulfonic acid polymer material, high-rate charging and discharging performance can be improved, capacity retention rate can be optimized, and the deficiencies of the prior art can be solved. Summary of the invention

[0007] The purpose of the present disclosure is to provide a composite electrode suitable for secondary batteries and a preparation method thereof. The conductive carbon is first pre-coated on the surface of the high-nickel positive electrode material NCM through a dry mechanofusion process (mechanofusion method) to improve the surface hydrophobicity of the high-nickel positive electrode material NCM and improve the coating of the subsequent lithiated perfluorosulfonic acid polymer (Li-Nafion) material, effectively maintaining the original spherical secondary particle morphology of the high-nickel positive electrode material NCM. The dry mechanofusion process has the characteristics of being fast and does not require additional solvents and gas protection. An appropriate amount of conductive carbon can be coated on the surface of the high-nickel positive electrode material NCM, improving the hydrophobicity of the positive electrode material surface, and improving the coating of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material on the surface of the high-nickel material NCM, but does not affect the morphology of the positive electrode material NCM. Furthermore, the use of lithiated perfluorosulfonic acid polymer (Li-Nafion) materials to replace the binders (PVDF, PAA, CMC-SBR...) used in traditional secondary battery processes, due to the excellent ion conductivity of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material, when the composite positive electrode plate is charged and discharged at a high rate (6CC / 6CD) can have a better capacity retention rate. In other words, by using the method of pre-surface treatment with conductive carbon, the functional coating lithiated perfluorosulfonic acid polymer (Li-Nafion) material can be more evenly coated on the surface of the high-nickel positive electrode material, and the performance of rapid charge and discharge and cycle life can be improved, thereby providing a fast and effective means to obtain a functional coating that can be used as an adhesive and evenly coated.

[0008] To achieve the above-mentioned purpose, the present disclosure provides a composite electrode including an electrode plate and a composite positive electrode material layer. The electrode plate has a bearing surface. The composite positive electrode material layer is coated on the bearing surface of the electrode plate, wherein the composite positive electrode material layer includes a plurality of positive electrode material particles, a first conductive carbon and a lithiated perfluorosulfonic acid polymer material. The plurality of positive electrode material particles are composed of a ternary material, wherein the composition of the ternary material is Li[Ni x Co y Mn zO2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2. The first conductive carbon is pre-coated on the surface of a plurality of cathode material particles by a dry mechanical mixing method, and the weight percentage of the first conductive carbon relative to the plurality of cathode material particles ranges from 1 wt.% to 5.5 wt.%. The lithiated perfluorosulfonic acid polymer (Li-Nafion) material coats the surface of the plurality of cathode material particles and adheres between the surfaces of the plurality of cathode material particles, and the weight percentage of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material relative to the plurality of cathode material particles ranges from 10 wt.% to 20 wt.%.

[0009] In one embodiment, the dry mechanical mixing method is a mechanical fusion mixing method, including mixing for 10 minutes at a first rotation speed of 600 rpm and mixing for 30 minutes at a second rotation speed of 4200 rpm, and having an operating temperature range between 30°C and 40°C.

[0010] In one embodiment, the lithiated perfluorosulfonic acid polymer material forms a lithiated perfluorosulfonic acid polymer solution through a mixed solvent and then is mixed with the plurality of cathode material particles and the first conductive carbon. The weight percentage concentration of the lithiated perfluorosulfonic acid polymer (Li-Nafion) solution is 10 wt.%, and the mixed solvent is composed of ethanol and n-butanol, where the weight ratio of ethanol to n-butanol is 1:2.

[0011] In one embodiment, the composite cathode material layer further includes a second conductive carbon, which is mixed with the plurality of cathode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material, and the weight percentage of the second conductive carbon relative to the plurality of cathode material particles ranges from 5.5 wt.% to 15 wt.%.

[0012] In one embodiment, the composite cathode material layer has a tap density range between 3.1 g / cm 3 to 3.3 g / cm 3 .

[0013] In one embodiment, the electrode plate is an aluminum plate.

[0014] In one embodiment, the plurality of cathode material particles have a first average particle size range between 10 μm and 20 μm, and the first conductive carbon has a second average particle size range between 50 nm and 200 nm.

[0015] To achieve the foregoing objectives, the present disclosure further provides a method for preparing a composite electrode, including the steps:

[0016] (a) Provide a plurality of cathode material particles and a first conductive carbon, wherein the plurality of cathode material particles are composed of a ternary material, and the composition of the ternary material is Li[Ni x Co y Mn z O2, and x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2; (b) Coating the first conductive carbon on the surface of the plurality of cathode material particles by a dry mechanical mixing method, wherein the weight percentage range of the first conductive carbon relative to the plurality of cathode material particles is between 1 wt.% and 5.5 wt.%; (c) Provide a lithiated perfluorosulfonic acid polymer (Li-Nafion) material, wherein the weight percentage range of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material relative to the plurality of cathode material particles is between 10 wt.% and 20 wt.%; (d) Mix the plurality of cathode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material to form a composite cathode material slurry; (e) Coating the composite cathode material slurry on a bearing surface of an electrode plate; and (f) Drying to form a composite electrode, wherein the lithiated perfluorosulfonic acid polymer material coats the surface of the plurality of cathode material particles and adheres between the surfaces of the plurality of cathode material particles.

[0017] In one embodiment, the dry mechanical mixing method in step (b) is a mechanical fusion mixing method, including mixing for 10 minutes at a first rotation speed of 600 rpm and mixing for 30 minutes at a second rotation speed of 4200 rpm, and having a working temperature range between 30 °C and 40 °C.

[0018] In one embodiment, in step (c), the lithiated perfluorosulfonic acid polymer material forms a lithiated perfluorosulfonic acid polymer solution through a mixed solvent, and the weight percentage concentration of the lithiated perfluorosulfonic acid polymer (Li-Nafion) solution is 10 wt.%, and the mixed solvent is composed of an ethanol and a n-butanol, wherein the weight ratio of ethanol: n-butanol is 1:2.

[0019] In one embodiment, a second conductive carbon is further added in step (d) to be mixed with the plurality of cathode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material, wherein the weight percentage range of the second conductive carbon relative to the plurality of cathode material particles is between 5.5 wt.% and 15 wt.%.

[0020] In one embodiment, in step (e), the composite cathode material slurry is coated on the bearing surface of the electrode plate by a doctor blade method, and the composite cathode material slurry has a surface density range between 9 mg / cm 2 to 12 mg / cm 2between.

[0021] In one embodiment, the composite cathode material layer has a compaction density ranging from 3.1 g / cm 3 Up to 3.3g / cm 3 .

[0022] In one embodiment, the electrode plate is an aluminum plate.

[0023] In one embodiment, the plurality of positive electrode material particles have a first average particle size ranging from 10 μm to 20 μm, and the first conductive carbon has a second average particle size ranging from 50 nm to 200 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of the composite electrode according to an embodiment of the present disclosure.

[0025] Figure 2 It is a schematic diagram revealing the structure of multiple positive electrode material particles.

[0026] Figure 3 It is a schematic diagram showing the structure of a plurality of positive electrode material particles pre-coated with a first conductive carbon.

[0027] Figure 4 is a SEM image revealing multiple cathode material particles.

[0028] Figure 5 is a SEM image showing a plurality of positive electrode material particles pre-coated with a first conductive carbon.

[0029] Fig. 6A It reveals the results of water droplet contact angle analysis after multiple positive electrode material particles were pressed into powder ingots.

[0030] Figure 6B The present invention discloses the result of water drop contact angle analysis after a plurality of positive electrode material particles pre-coated with a first conductive carbon are pressed into powder.

[0031] Figure 7 The chemical formula structure of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material is revealed.

[0032] Figure 8 The present invention is a flow chart of a method for preparing a composite electrode according to an embodiment of the present invention.

[0033] Fig. 9 The SEM / EDS analysis results of the comparative example.

[0034] Fig.10 The SEM / EDS analysis results of the disclosed examples.

[0035] Fig.11AThis is a charge and discharge cycle test chart of the comparative example at 0.1C / 1C / 3C / 5C / 6C.

[0036] Fig. 11B The following is a test chart showing the charge and discharge cycles at 0.1C / 1C / 3C / 5C / 6C.

[0037] Fig. 11C It is a comparison chart of the specific capacity of the comparative example and the exemplary example at 3C charge and discharge.

[0038] Fig.11D It is a comparison chart of the specific capacity of the comparative example and the exemplary example at 6C charge and discharge.

[0039] Fig.12 It is a charge-discharge cycle test diagram obtained under 1CC / 1CD cycle test conditions for the comparative example and the demonstration example.

[0040] Fig.13 It is a charge-discharge cycle test diagram obtained under 6CC / 6CD cycle test conditions for the comparative example and the demonstration example.

[0041] Fig.14 This is a charge and discharge cycle test graph obtained under 1CC / 1CD cycle test conditions for the first PVDF comparison example and the second PVDF comparison example.

[0042] Fig.15 This is the charge and discharge cycle test graph obtained under the 6CC / 6CD cycle test conditions for the first PVDF comparative example and the second PVDF comparative example.

[0043] Description of reference numerals:

[0044] 1: Composite electrode

[0045] 2: Electrode plate

[0046] 3: Composite positive electrode material layer

[0047] 10: Positive electrode material particles

[0048] 20: First carbon guide

[0049] 21: Load-bearing surface

[0050] 30: Li-Nafion material

[0051] 31: Long chain hydrophobic segment

[0052] 40: Second carbon guide

[0053] S1~S6: Steps DETAILED DESCRIPTION

[0054] Some typical embodiments that embody the features and advantages of the present disclosure will be described in detail in the following description. It should be understood that the present disclosure can have various changes in different embodiments, all of which do not depart from the scope of the present disclosure, and the description and drawings therein are essentially used for illustrative purposes rather than for limiting the present disclosure. For example, if the following content of the present disclosure describes that a first feature is set on or above a second feature, it means that it includes an embodiment in which the first feature and the second feature are directly in contact, and also includes an embodiment in which an additional feature can be set between the first feature and the second feature, so that the first feature and the second feature may not be in direct contact. In addition, it is understood that although the terms "first", "second", "third" and the like can be used in the claims to describe different components, these components should not be limited by these terms, and the components described in the embodiments are represented by different component symbols. These terms are used to distinguish different components, for example: the first component can be referred to as the second component. Similarly, the second component can also be referred to as the first component without departing from the scope of the embodiments. The term "and / or" in the specification includes any or all combinations of one or more related listed items. The term "approximately" refers to an average value within a standard error range generally accepted by those of ordinary skill in the art. Unless otherwise specified in the operation / working examples or otherwise explicitly stated, all numerical ranges, quantities, values ​​and percentages disclosed in the present disclosure (e.g., angles, lengths of time, temperatures, operating conditions, quantity ratios, etc.) should be understood to be modified by the term "approximately" or "substantially" in all embodiments. Therefore, unless otherwise specified, the numerical parameters stated in the present disclosure and the appended claims are approximate values ​​that may vary as needed. For example, the number of significant digits of each numerical parameter should be interpreted at least by applying ordinary rounding. The range can be expressed herein as from one endpoint to another or between two endpoints. Unless otherwise specified, all ranges disclosed herein include endpoints.

[0055] Figure 1 Schematic diagram of the structure of the composite electrode of the embodiment of the present disclosure. In the present embodiment, the present disclosure provides a composite electrode 1, which is a positive electrode suitable for a traditional lithium battery or a lithium metal battery. In the present embodiment, the composite electrode 1 includes an electrode plate 2 and a composite positive electrode material layer 3. The electrode plate 2 is, for example, a current collector of an aluminum plate, having a bearing surface 21. The composite positive electrode material layer 3 is coated on the bearing surface 21 of the electrode plate 2 using the preparation method of the composite positive electrode disclosed in the present disclosure. The composite positive electrode material layer 3 obtained by the preparation method of the composite positive electrode disclosed in the present disclosure includes a plurality of positive electrode material particles 10, a first conductive carbon 20 and a lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30. In the present embodiment, the plurality of positive electrode material particles 10 are composed of a ternary material, wherein the composition of the ternary material is Li[Nix Co y Mn z O2, and x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2, with a high nickel content (nickel content > 80%). It should be noted that in this embodiment, the first conductive carbon 20 is also pre-coated on the surface of a plurality of cathode material particles 10 by a dry mechanical mixing method such as a mechanical fusion mixing method, wherein the weight percentage range of the first conductive carbon 20 relative to the plurality of cathode material particles 10 is between 1 wt.% and 5.5 wt.%. Figure 2 is a schematic structural diagram showing a plurality of cathode material particles. Figure 3 is a schematic structural diagram showing a plurality of cathode material particles pre-coated with the first conductive carbon. By using the mechanical fusion method to pre-coat the first conductive carbon 20 on the surface of a plurality of cathode material particles 10, the first conductive carbon 20 can be evenly distributed on the surface of the plurality of cathode material particles 10 in a dot-like form. In addition to reducing the influence of uneven distribution of the conductive carbon on the electrical performance during electrode fabrication, it also further changes the surface properties of the plurality of cathode material particles 10.

[0056] Figure 4 is an SEM image showing a plurality of cathode material particles. Figure 5 is an SEM image showing a plurality of cathode material particles pre-coated with the first conductive carbon. In this embodiment, the plurality of cathode material particles 10 have a first average particle size range between 10 μm and 20 μm, and the first conductive carbon 20 has a second average particle size range between 50 nm and 200 nm. After the plurality of cathode material particles 10 are treated by the mechanical fusion mixing method and the first conductive carbon 20 is evenly distributed on the surface of the plurality of cathode material particles 10 in a dot-like manner, the morphology and particle size of the plurality of cathode material particles 10 are not changed.

[0057] Fig. 6A is the result of the water droplet contact angle analysis after the plurality of cathode material particles are pressed into a powder tablet. Figure 6B is the result of the water droplet contact angle analysis after the plurality of cathode material particles pre-coated with the first conductive carbon are pressed into a powder tablet. Among them, the water droplet contact angle obtained after the plurality of cathode material particles 10 (with the structure as Figure 2 shown) are pressed into a powder tablet is about 10°, as Fig. 6A shown. And the water droplet contact angle obtained after the plurality of cathode material particles 10 pre-coated with the first conductive carbon 20 (with the structure as Figure 3 shown) are pressed into a powder tablet is about 27°, as Figure 6B shown. Comparing the two results, it can be seen that when the plurality of cathode material particles 10 are pre-coated with the first conductive carbon 20 by the mechanical fusion method, the hydrophobicity of the surface of the plurality of cathode material particles 10 can be increased. Figure 7It reveals the chemical formula structure of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material. As shown in the figure, the structure of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 includes a long-chain hydrophobic segment 31. Therefore, after the first conductive carbon 20 is coated on the surface of multiple cathode material particles 10 by the mechanical fusion method, the surface of the multiple cathode material particles 10 can be modified to exhibit higher hydrophobicity. In this way, it is more conducive to the combination of the multiple cathode material particles 10 and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30. Of course, the types, composition ratios, and material properties of the multiple cathode material particles 10 pre-coated with the first conductive carbon 20 and the mixed lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 selected for the composite cathode material layer 3 of the present disclosure can be adjusted according to actual application requirements and are not limited thereto. The preparation method of the composite electrode 1 of the present disclosure will be described below.

[0058] Figure 8 It is a flowchart of the preparation method of the composite electrode according to an embodiment of the present disclosure. In this embodiment, first, as shown in step S1, multiple cathode material particles 10 and the first conductive carbon 20 are provided. Among them, the multiple cathode material particles are composed of a ternary material, and the composition of the ternary material is Li[Ni x Co y Mn z O2, and x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2. In this embodiment, the multiple cathode material particles 10 have a first average particle size range between 10 μm and 20 μm. The first conductive carbon 20 is, for example, a conductive carbon black (Super-P) and has a second average particle size range between 50 nm and 200 nm.

[0059] Next, as shown in step S2, multiple cathode material particles 10 and the first conductive carbon 20 in a specific ratio can be coated with the first conductive carbon 20 on the surface of the multiple cathode material particles 10 by, for example, a dry mechanical fusion mixing method, and the obtained structure is as Figure 3As shown. In this embodiment, the weight percentage of the first conductive carbon 20 relative to the plurality of positive electrode material particles 10 ranges from 1wt.% to 5.5wt.%. Thus, an appropriate amount of the first conductive carbon 20 can be evenly distributed on the surface of the plurality of positive electrode material particles 10 in a dot-like form, thereby completing the surface modification of the plurality of positive electrode material particles 10 without changing the morphology and particle size of the plurality of positive electrode material particles 10. It is worth noting that the weight percentage of the first conductive carbon 20 relative to the plurality of positive electrode material particles 10 is less than 5.5wt.%, which can avoid the first conductive carbon 20 from excessively coating the surface of the plurality of positive electrode material particles 10 and affecting the subsequent mixed coating of the lithium-containing perfluorosulfonic acid polymer (Li-Nafion) material 30. On the other hand, when the surface modification is performed by mechanical fusion mixing, the mixing process is also mixed at a first speed of 600rpm for 10 minutes and at a second speed of 4200rpm for 30 minutes, and has an operating temperature range of 30°C to 40°C. By controlling the mixed surface modification and pre-coating method, working temperature, rotation speed and time, structural defects caused by high temperature and excessive friction between particles can be prevented, while ensuring that the plurality of positive electrode material particles 10 can exert the surface modification effect through the pre-coating of the first conductive carbon 20.

[0060] In addition, in this embodiment, a lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 is provided, as shown in step S3. In order to obtain a good coating effect, the weight percentage range of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 relative to the plurality of positive electrode material particles 10 is preferably between 10wt.% and 20wt.%. In addition, in this embodiment, the lithiated perfluorosulfonic acid polymer material 30 can also form a lithiated perfluorosulfonic acid polymer solution through a mixed solvent, and the weight percentage concentration of the lithiated perfluorosulfonic acid polymer (Li-Nafion) solution is 10wt.%. The mixed solvent can be composed of an ethanol and a n-butanol, wherein the weight ratio of ethanol:n-butanol is 1:2. Of course, the present disclosure is not limited thereto.

[0061] Thereafter, in step S4, the plurality of positive electrode material particles 10 pre-coated with the first conductive carbon 20 obtained in step S2 and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 provided in step S3 are mixed to form a composite positive electrode material slurry. It is worth noting that in some embodiments, the composite positive electrode material layer 3 in the composite electrode 1 needs to add a higher conductive carbon content, and exceeds the content of the first conductive carbon 20 in step S2, then the additional conductive carbon content can be added in step S4 by adding the second conductive carbon 40, so as to be mixed with the plurality of positive electrode material particles 10 pre-coated with the first conductive carbon 20 and the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30. Of course, the weight percentage of the second conductive carbon 40 relative to the plurality of positive electrode material particles 10 can be adjusted according to the actual application requirements, preferably in the range of 5.5wt.% to 15wt.%.

[0062] In step S5, the composite positive electrode material slurry is coated on a supporting surface 21 of an electrode plate 2. The composite positive electrode material slurry is coated on the supporting surface 21 of the electrode plate 2 by a doctor blade. Preferably, the composite positive electrode material slurry coated on the supporting surface 21 of the electrode plate 2 has a surface density ranging from 9 mg / cm 2 Up to 12mg / cm 2 Of course, the present disclosure is not limited thereto.

[0063] Finally, in step S6, the composite positive electrode material slurry coated on the electrode plate 2 can be dried to form a composite electrode 1. The resulting structure is as follows: Figure 1 As shown, the lithiated perfluorosulfonic acid polymer material 30 covers the surfaces of the plurality of positive electrode material particles 10 and adheres between the surfaces of the plurality of positive electrode material particles 10 .

[0064] In one example, 495 g of NCM material is used to provide a plurality of positive electrode material particles 10. The NCM material has a chemical formula of Li[Ni 0.83 Co 0.12 Mn 0.05]O2 (Ni:Co:Mn=83:12:5) and surface area BET=0.32m2 / g. In addition, 27.5g of conductive carbon black (Super-P) is taken to provide the first conductive carbon 20 as a precursor for surface modification of multiple positive electrode material particles 10. 495g of NCM material and 27.5g of conductive carbon black (Super-P) are treated by mechanical fusion mixing method. First, the output power is low to 7.5%, that is, mixed at a speed of 600rpm for 10 minutes, and then the output power is set to 80%, that is, mixed at a speed of about 4200rpm for 30 minutes. In order to avoid the adverse effects of high temperature generated by high-speed mixing on the sample, the temperature of the equipment is controlled at 30℃~40℃ during the mixing process. The surface-modified sample obtained is as follows Figure 5 As shown, it is called NCM@C.

[0065] In addition, the lithiated perfluorosulfonic acid polymer (Li-Nafion) material 30 is provided in the form of a solution. When preparing the lithiated perfluorosulfonic acid polymer solution, first weigh 20.981g of LiOH·H2O powder into a 500mL quantitative bottle, and add 300mL of deionized water. After the LiOH·H2O is completely dissolved, quantify it to 500mL with deionized water to complete the preparation of 1N LiOH solution. Take another 250mL round-bottom flask and weigh 60g of 5% H-Nafion solution into the round-bottom flask, and titrate it with the above 1N LiOH solution to pH = 6. Then, the above-mentioned Li-Nafion solution that has been titrated is concentrated under reduced pressure at 60°C to 80°C to completely dry the solvent. Finally, after the solvent is removed, a mixed solvent of ethanol: n-butanol in a weight ratio of 1:2 is added, and the weight percentage concentration of Li-Nafion is 10wt.%, and the pre-lithiated Li-Nafion solution can be obtained after it is completely dissolved.

[0066] When preparing the composite electrode 1, weigh NCM@C: Super-P (as the second conductive carbon): 10wt.% Li-Nafion solution = 8.42g: 0.58g: 10g respectively, put them into a mixing bottle, mix them with a planetary rotating stirrer, set the speed to 1200rpm and the mixing time to 10min, and then obtain the composite positive electrode material slurry. The composite positive electrode material slurry is evenly coated on the Al foil with a doctor blade coater, and the surface density is controlled at 9mg / cm 2 ~12mg / cm 2 The coated electrode semi-finished product is dried at 100°C for 1 hour. The dried electrode semi-finished product is rolled by a pole piece rolling machine. The compaction density is controlled at 3.1g / cm during the rolling process. 3 ~3.3g / cm 3, that is, the composite electrode 1 of the present disclosure is manufactured. The composite electrode 1 is cut into a circular electrode with a diameter of 1 cm by a pole piece cutter, and can be used for electrochemical analysis with a CR2032 button cell.

[0067] In a comparative example, the same positive electrode material but the surface modification of the NCM material is omitted, which is referred to as NCM. When making the comparative example electrode, NCM: Super-P (as conductive carbon): 10wt.% Li-Nafion solution = 8g: 1g: 10g are weighed respectively, and then placed in a mixing bottle, and mixed with a planetary rotating stirrer, and the speed is set to 1200rpm and the mixing time is 10min. The comparative example slurry is evenly coated on the Al foil with a doctor blade coater, and the surface density is controlled at 9mg / cm 2 ~12mg / cm 2 The coated electrode semi-finished product is dried at 100°C for 1 hour. The dried electrode semi-finished product is rolled by a pole piece rolling machine. The compaction density is controlled at 3.1g / cm during the rolling process. 3 ~3.3g / cm 3 The comparative example electrode is cut into a circular electrode with a diameter of 1 cm by a pole piece cutter, and then the electrochemical analysis can be performed on a CR2032 button cell.

[0068] First, the distribution of Ni and F in the comparative example and demonstration samples was analyzed using SEM / EDS. Fig. 9 The SEM / EDS analysis results of the comparative example are shown in the cross section of the electrode plate of the comparative example. Since the F element is mainly provided by the Li-Nafion material and the Ni element is provided by the NCM material, it can be seen from the figure that the F signal and the Ni signal do not overlap, which means that the Li-Nafion material is not evenly coated on the surface of the NCM material. In addition, Fig.10 The SEM / EDS analysis results of the exemplary embodiment of the present disclosure are shown in the figure. As shown in the figure, the F signal and the Ni signal overlap, indicating that the Li-Nafion material is uniformly coated on the surface of the NCM material. It can be seen that after the surface of the NCM material is first modified by the mechanical fusion mixing method disclosed in the present disclosure to assist the carbon, the resulting NCM@C material is easier to combine with the Li-Nafion material in the subsequent mixing process, so that the Li-Nafion material is uniformly coated on the surface of the NCM@C material.

[0069] For the CR2032 button-type batteries obtained in the comparative example and the exemplary example, the charge and discharge performance can be analyzed at different charge and discharge rates, such as 0.1C, 1C, 3C, 5C, and 6C. Fig.11A This is a charge and discharge cycle test chart of the comparative example at 0.1C / 1C / 3C / 5C / 6C. Fig. 11B The following is a test chart showing the charge and discharge cycles at 0.1C / 1C / 3C / 5C / 6C. Fig. 11C It is a comparison chart of the specific capacity of the comparative example and the exemplary example at 3C charge and discharge. Fig.11D The comparative example and the exemplary example are compared in specific capacity at 6C charge and discharge. Table 1 lists the analysis results of the comparative example and the exemplary example at 3C / 5C / 6C charge and discharge rates. FIG. 11A to FIG. 11D The results listed in Table 1 show that at high charge and discharge rates (above 3C), the Li-Nafion material of the exemplary example is evenly coated on the surface of the NCM@C material, and has better charge and discharge performance.

[0070] Table 1 is a comparison of charge and discharge capacities at different charge and discharge rates

[0071]

[0072] Fig.12 It is a charge-discharge cycle test diagram obtained under the 1CC / 1CD cycle test conditions for the comparative example and the demonstration example. Under the 1CC / 1CD cycle test conditions, the capacity retention rate of the comparative example after 100 cycles is 88%, while the capacity retention rate of the demonstration example after 100 cycles is 91%. Different from the comparative example in which the NCM material is directly coated with Li-Nafion material, the present disclosure uses a mechanical fusion mixing method to pre-mix the conductive carbon and the NCM material to obtain the NCM@C material, and also increases the uniformity of the Li-Nafion material coated on the surface of the positive electrode material particles, which can not only increase the performance of high-rate charge and discharge, but also improve the life of the charge and discharge cycle.

[0073] Fig.13 It is a charge and discharge cycle test diagram obtained by the comparative example and the demonstration example under the 6CC / 6CD cycle test conditions. Under the 6CC / 6CD cycle test conditions, the capacity retention rate of the comparative example after 100 cycles is 74%, while the capacity retention rate of the demonstration example after 100 cycles is 84%. Compared with the comparative example, the cycle life of the demonstration example for rapid charge and discharge is significantly improved. In other words, the present disclosure uses a mechanical fusion mixing method to pre-mix the conductive carbon to improve the uniformity of the Li-Nafion material coating the positive electrode material, which not only improves the ion conduction rate, but also significantly slows down the capacity decay of the positive electrode material.

[0074] In addition, it should be noted that the present disclosure uses a dry mechanical fusion method to mix conductive carbon to perform pretreatment of the surface modification of the positive electrode material particles, and it is performed on Li-Nafion materials with long-chain hydrophobic segments. Under the same preparation conditions, the adhesive Li-Nafion material used in the aforementioned comparative example is replaced with PVDF to obtain a first comparative example of PVDF. In addition, the NCM@C material obtained by pre-mixing conductive carbon and NCM material by mechanical fusion mixing method, and then replacing the Li-Nafion material with PVDF as an adhesive, the obtained PVDF-coated NCM@C material sample can obtain a second comparative example of PVDF. Fig.14 This is a charge and discharge cycle test graph obtained under 1CC / 1CD cycle test conditions for the first PVDF comparison example and the second PVDF comparison example. Fig.15 This is the charge and discharge cycle test diagram of the first PVDF comparative example and the second PVDF comparative example under the 6CC / 6CD cycle test conditions. Figures 13 to 15 It can be seen that if PVDF is used to replace Li-Nafion material as an adhesive, even if the surface of the positive electrode material particles is pretreated by mixing conductive carbon with dry mechanical fusion, the resulting composite electrode does not show improvement in cycle life at high charge and discharge rates. In other words, the surface of the positive electrode material particles is pretreated by mixing conductive carbon with dry mechanical fusion, which is more suitable for the application of Li-Nafion material. Of course, Li-Nafion material may also be replaced by other polymer adhesives with long-chain hydrophobic segments. I will not go into details here.

[0075] In summary, the present disclosure provides a composite electrode suitable for secondary batteries and a preparation method thereof. The conductive carbon is first pre-coated on the surface of the high-nickel positive electrode material NCM through a dry mechanofusion method to enhance the surface hydrophobicity of the high-nickel positive electrode material NCM and enhance the coating property of the subsequent lithiated perfluorosulfonic acid polymer (Li-Nafion) material, thereby effectively maintaining the original spherical secondary particle morphology of the high-nickel positive electrode material NCM. The dry mechanofusion process is fast and does not require additional solvents and gas protection. An appropriate amount of conductive carbon can be coated on the surface of the high-nickel positive electrode material NCM, thereby enhancing the hydrophobicity of the surface of the positive electrode material and enhancing the coating property of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material on the surface of the high-nickel material NCM, but does not affect the morphology of the positive electrode material NCM. Furthermore, the use of lithiated perfluorosulfonic acid polymer (Li-Nafion) materials to replace the binders (PVDF, PAA, CMC-SBR...) used in traditional secondary battery processes, due to the excellent ion conductivity of the lithiated perfluorosulfonic acid polymer (Li-Nafion) material, when the composite positive electrode plate is charged and discharged at a high rate (6CC / 6CD) can have a better capacity retention rate. In other words, by using the method of pre-surface treatment with conductive carbon, the functional coating lithiated perfluorosulfonic acid polymer (Li-Nafion) material can be more evenly coated on the surface of the high-nickel positive electrode material, and the performance of rapid charge and discharge and cycle life can be improved, thereby providing a fast and effective means to obtain a functional coating that can be used as an adhesive and evenly coated.

[0076] The present disclosure may be modified in various ways by those skilled in the art without departing from the scope of protection of the claims.

Claims

1. A composite electrode comprising: An electrode plate having a bearing surface; as well as A composite positive electrode material layer is coated on the supporting surface of the electrode plate, wherein the composite positive electrode material layer comprises: A plurality of positive electrode material particles are formed by a ternary material, wherein the composition of the ternary material is Li[Ni x Co y Mn z ]O2, and x+y+z=1,0.8 <x<1,0<y<0.2,0<z<0.2; A first conductive carbon is pre-coated on the surface of the plurality of positive electrode material particles by a dry mechanical mixing method, wherein the weight percentage of the first conductive carbon relative to the plurality of positive electrode material particles ranges from 1wt.% to 5.5wt.%; and A lithiated perfluorosulfonic acid polymer material covers the surfaces of the plurality of positive electrode material particles and is bonded between the surfaces of the plurality of positive electrode material particles, wherein the weight percentage of the lithiated perfluorosulfonic acid polymer material relative to the plurality of positive electrode material particles ranges from 10wt.% to 20wt.%.

2. The composite electrode as claimed in claim 1, wherein the dry mechanical mixing method is a mechanical fusion mixing method, comprising mixing at a first rotation speed of 600 rpm for 10 minutes and mixing at a second rotation speed of 4200 rpm for 30 minutes, and having an operating temperature range of 30°C to 40°C.

3. The composite electrode as claimed in claim 1, wherein the lithiated perfluorosulfonic acid polymer material is formed into a lithiated perfluorosulfonic acid polymer solution through a mixed solvent and then mixed with the plurality of positive electrode material particles and the first conductive carbon, the weight percentage concentration of the lithiated perfluorosulfonic acid polymer solution is 10wt.%, and the mixed solvent is composed of ethanol and n-butanol, wherein the weight ratio of the ethanol: the n-butanol is 1:

2.

4. The composite electrode as described in claim 1, wherein the composite positive electrode material layer further includes a second conductive carbon, which is mixed with the plurality of positive electrode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer material, wherein the weight percentage of the second conductive carbon relative to the plurality of positive electrode material particles ranges from 5.5wt.% to 15wt.%.

5. The composite electrode as claimed in claim 1, wherein the composite positive electrode material layer has a compaction density ranging from 3.1 g / cm 3 Up to 3.3g / cm 3 . The composite electrode as claimed in claim 1 , wherein the electrode plate is an aluminum plate. 7 . The composite electrode as claimed in claim 1 , wherein the plurality of positive electrode material particles have a first average particle size ranging from 10 μm to 20 μm, and the first conductive carbon has a second average particle size ranging from 50 nm to 200 nm.

8. A method for preparing a composite electrode, comprising the steps of: (a) providing a plurality of positive electrode material particles and a first conductive carbon, wherein the plurality of positive electrode material particles are composed of a ternary material, wherein the composition of the ternary material is Li[Ni x Co y Mn z ]O2, and x+y+z=1,0.8 <x<1,0<y<0.2,0<z<0.2; (b) coating the first conductive carbon on the surface of the plurality of positive electrode material particles by a dry mechanical mixing method, wherein the weight percentage of the first conductive carbon relative to the plurality of positive electrode material particles ranges from 1 wt.% to 5.5 wt.%; (c) providing a lithiated perfluorosulfonic acid polymer material, wherein the weight percentage of the lithiated perfluorosulfonic acid polymer material relative to the plurality of positive electrode material particles ranges from 10 wt.% to 20 wt.%; (d) mixing the plurality of positive electrode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer material to form a composite positive electrode material slurry; (e) coating the composite positive electrode material slurry on a supporting surface of an electrode plate; and (f) drying to form the composite electrode, wherein the lithiated perfluorosulfonic acid polymer material covers the surfaces of the plurality of positive electrode material particles and adheres between the surfaces of the plurality of positive electrode material particles.

9. The method for preparing a composite electrode as described in claim 8, wherein the dry mechanical mixing method of step (b) is a mechanical fusion mixing method, comprising mixing at a first rotation speed of 600 rpm for 10 minutes and mixing at a second rotation speed of 4200 rpm for 30 minutes, and having an operating temperature range of 30°C to 40°C.

10. The method for preparing a composite electrode as claimed in claim 8, wherein in the step (c), the lithiated perfluorosulfonic acid polymer material is formed into a lithiated perfluorosulfonic acid polymer solution by a mixed solvent, the weight percentage concentration of the lithiated perfluorosulfonic acid polymer solution is 10wt.%, and the mixed solvent is composed of ethanol and n-butanol, wherein the weight ratio of the ethanol to the n-butanol is 1:

2.

11. The method for preparing a composite electrode as claimed in claim 8, wherein in step (d), a second conductive carbon is further added to be mixed with the plurality of positive electrode material particles pre-coated with the first conductive carbon and the lithiated perfluorosulfonic acid polymer material, wherein the weight percentage of the second conductive carbon relative to the plurality of positive electrode material particles ranges from 5.5wt.% to 15wt.%.

12. The method for preparing a composite electrode as claimed in claim 8, wherein the step (e) is to apply the composite positive electrode material slurry to the supporting surface of the electrode plate by a scraper forming method, and the composite positive electrode material slurry has a surface density ranging from 9 mg / cm 2 Up to 12mg / cm 2 between.

13. The method for preparing a composite electrode as claimed in claim 8, wherein the composite positive electrode material layer has a compaction density ranging from 3.1 g / cm 3 Up to 3.3g / cm 3 .

14. The method for preparing a composite electrode as claimed in claim 8, wherein the electrode plate is an aluminum plate. 15 . The method for preparing a composite electrode as claimed in claim 8 , wherein the plurality of positive electrode material particles have a first average particle size ranging from 10 μm to 20 μm, and the first conductive carbon has a second average particle size ranging from 50 nm to 200 nm.